FUNGSI PEMERINTAH DAERAH KABUPATEN SABU RAIJUA DALAM PEMBENTUKAN PERATURAN TENTANG PENERTIBAN PERJUDIAN DI KABUPATEN SABU RAIJUA - Mangngi, Fivin F; Yohanes, Saryono; Ratu Udju, Hernimus (Petitum Law Journal, 2025)
In the context of the implementation of local government in accordance with the mandate of the Constitution of the Republic of Indonesia in 1945, Local governments follow the principles of autonomy and assistance duties while regulating and managing their own government issues. Furthermore, local governments are instructed to increase regional competitiveness by paying attention to the principles of democracy, equity, justice, privileges, and regional specificity within the framework of the Unitary State of the Republic of Indonesia. They are also instructed to expedite the realization of community welfare through improvement, service, empowerment, and community participation. As stated in Article 236 paragraph (1) of Law Number 32 of 2004 concerning Regional Government, Regional Regulations are established for the implementation of regional autonomy and assistance tasks. Therefore, in order to implement regional autonomy in Sabu Raijua Regency, it is necessary to have a Regional Regulation made by the local government of Sabu Raijua Regency. In addition to Regional Regulations, the Sabu Raijua community also has other regulations in the region such as regional head regulations, village regulations, customs and so on. The results of the study stated that in carrying out its function as a regulator on gambling control in Sabu Raijua Regency, the government has not carried out its duties properly. The government has not established a Regional Regulation on Gambling Control due to the low quality of human resources, the absence of participation from the community and the lack of availability of funds in Sabu Raijua Regency.